Post-collisional magmatism associated with the final closure of the Rushan-Pshart Meso-Tethys Ocean in Pamir, Tajikistan: Inference from Cretaceous igneous rocks of the Pshart accretionary complex - Yogibekov, Dzhovid; Sang, Miao; Xiao, Wenjiao; Mamadjonov, Yunus; Zhou, Chuanming; Yang, He; Mao, Qigui; Aminov, Jovid; Khalimov, Gufron; Ashuraliev, Sohibnazar (Frontiers in Earth Science, 2023)
The Pamir orogen was formed by subducted-accretion and amalgamation of Cimmerian terranes from norther margin of Gondwana with the southern margin of Eurasia. The Mesozoic magmatic rocks are widespread in Pamir and record the tectonic evolution in different stages. The Rushan-Pshart suture zone represented an ancient ocean between the Central and Southern Pamir. In this paper, we report petrography, geochronology and geochemistry of Cretaceous granites and diabase dikes that intrude into the Pshart complex. The granites emplaced between 124-118 Ma, based on their zircon U-Pb ages. These granites are characterized by high-K calc-alkaline, low magnesian, and have high value of SiO2, A/CNK and K2O+Na2O. They display strong depletion on Ba, Sr, Eu, Ti and comparatively weak negative anomaly of Nb in spidergram, and are proposed here to be highly-fractionated strongly peraluminous S-type granites. They have been generated by partial melting of the metasedimentary rocks in plagioclase stability field and underwent subsequent fractional crystallization during their ascent. The diabase dikes contain low SiO2, and high MgO, negative anomaly on Nb and Ta, and interpreted to form in an extensional environment. Late Jurassic-Early Cretaceous closure of the Rushan-Pshart Ocean and subsequent foundering its oceanic lithosphere caused local extension and upwelling of asthenospheric mantle. Underplating of mafic magma provided heat source to make metasedimentary derived granitic melt that formed in initial post-collisional environment. The subsequent local extension caused the emplacement of diabase dikes. Based on our new data, combined with previous studies, we concluded that the Rushan-Pshart suture zone is the remnant of the Meso-Tethys Ocean, and it may represent the western continuation of the Bangong-Nujiang suture of the Tibetan Plateau.